Mulheres e política no estado da Paraíba: a atuação de Lúcia Braga em meio às práticas políticas locais - Rodrigues, Dayanny Deyse Leite (2017)
The objective of this paper was to analyses the actions of Lúcia Braga between the years of 1982 and 1988, in which it enters the field of politics. In the year of 2017, the right of the vote for the women, sanctioned with the law nº. 21.076/32, completes 85 years old. Until that time, the political participation was closed for the women, and this space was occupied principally for the men. In this way, the women fought for more rights and changed the rules. They were searching to defense the female participation in the political field. Growing in a gradual mode since the conquest of the right to vote, we observes the progresses in the women participation in the political world especially after the 1980’s decade, time when, for the first time, some parties started to have the feminist flags in their political programs. In this context, Antônia Lúcia Navarro Braga started her way in the political field. Her role can’t be forget, but we also can’t forget that, same with her apparent political autonomy, Lúcia Braga never cuts her relationships with the oligarchies of her time. Like first lady of the state, Lúcia Braga used a lot of the conservative political practices for to effective her actions. Welfare and populists practices were observed in the development of the actions of Lúcia Braga and her group in the Funsat, like the distribution of staple basked products, materials for construction, the development of the project Multirão, whose methodology of work can be appointed like a exploration of the worked force of the clients. With the actuation near to the peripheral population of the state, started with her work at Funsat, that Lúcia Braga turned herself in a important political name in Paraíba in the middle of the decade of 1980. The intention is not to forget the political capital of the family which Lúcia Braga had, I show the experiences of her and her work in the Social Foundation of Work like important constructs of the political capitals of that first lady. This work is inside of the perspective of the Political History, but not that of the 19th century, made for the institutions of the state, for the events of the the short duration or for the big events, describes for the first generation of the Annales like “factual, idealist and psychologist”. It works in the perspective of the New Political History, which appears in the 1980’s, using the questions of the Social Sciences and the Political Science, answering to the new propositions of the New Cultural History. In this perspective, the conception of “Political Capital” was in all paper. The documentation was composed for three autobiographic books, Time to live time to tell, The house of the palm-trees, Our blunders of each day and other histories, texts published in the local press, like the newspapers A União, O Norte, O Momento, o Correio da Paraíba. Inside of that, the Revista da Funsat. With that information, the data of the High Electoral Tribunal and the Regional Electoral Tribunal of Paraíba.